Critical Success Factors of Agile Innovation Management in the Government of Palu Municipality in Central Sulawesi Province - Halim, Rahmawati, RHM; Tahili, Mashuri H., MHT (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
Agile governance plays a crucial role in developing agile innovation to enhance performance in Palu Municipality. This study examines the critical success factors of agile innovation management (AIM) in the government of Palu Municipality. This study employed an exploratory survey and a quantitative method to collect data through questionnaires, with analysis conducted using the Structural Equation Modeling (SEM) method. The findings identify end-user involvement, technology development, organizational innovation, and agile methodology for service innovation as crucial success elements in achieving effective AIM